Anxiety Symptoms and Disease Severity in Children and Adolescents With Crohn Disease. Issue 1 (January 2015) - Reigada, Laura C.; Hoogendoorn, Claire J.; Walsh, Lindsay C.; Lai, Joanne; Szigethy, Eva; Cohen, Barry H.; Bao, Ruijun; Isola, Kimberly; Benkov, Keith J.
ABSTRACT: Objectives: Children and adolescents diagnosed as having Crohn disease (CD), a type of inflammatory bowel disease (IBD), have increased vulnerability for anxiety symptoms that may be related to disease-related processes. The aims of this article are 3-fold: to report the proportion of pediatric patients with CD whose self-reported anxiety symptoms are indicative of distress, to describe the constellation of anxiety symptoms, and to examine the relation between anxiety and disease symptoms. Methods: Retrospective medical chart review was performed for 93 youths with CD (ages 9–18 years) who had completed the Screen for Child Anxiety Related Disorders during their gastroenterology visit. Medical records were reviewed for demographic and disease characteristics. the Harvey-Bradshaw Index (HBI) was used as a measure of CD activity. Results: Thirty percent of the youths reported experiencing elevated anxiety symptoms (Screen for Child Anxiety Related Disorder score >20), and 50% had scored above the cutoff in 1 or more anxiety domains, with school anxiety, general anxiety, and separation anxiety symptoms reported most frequently. Youth rated with moderate/severe disease activity on the HBI (n = 4) self-reported more anxiety symptoms compared with youth with inactive disease (n = 78, P = 0.03). Greater school anxiety was significantly associated with decreased well-being ( P = 0.003), more abdominal pain ( P < 0.001), and the number of loose stools ( P = 0.01). Having extraintestinal symptoms was significantly associated with higher somatic/panic anxiety ( P = 0.01). Conclusions: Implementing a brief anxiety screen in tertiary pediatric settings may be one approach to identify young patients with CD in distress. Health care providers should consider periodic assessment of school anxiety among youth with CD.